Morphological and biochemical analysis of the stored and larval food of an obligate necrophagous bee, Trigona hypogea - Serrao, J. E.; da Cruz-Landim, C.; Silva-de-Moraes, RLM (Birkhauser Verlag Ag, 1997)
Trigona hypogea, T. crassipes, and T. necrophaga are obligate necrophagous bees that differ from the majority of bees by using animal material instead of pollen as a protein resource. Since T. hypogea does not store protein in cerumen pots, it was thought that glandular secretions were its only larval protein source. This is in contrast to T. necrophaga which stores a yellowish proteinaceous jelly in the pots. Our results show that the larval food of T. hypogea has a higher protein content than the food stored in the pots and that it presents an electrophoretical protein pattern similar to that of the hypopharyngeal gland, indicating that workers add glandular secretions to the larval food while provisioning the brood cells. Thus, it can be suggested that T. hypogea has a provisioning behavior similar to other Meliponinae. The presence of several bands of proteins in the food stored in the pots shows that this species stores carrion mixed with honey in storage pots. Morphological data suggest that both larvae and adults make use of the same foodstuffs. These results also suggest that T. hypogea is more similar to other necrophagous species than it is to T. necrophaga (a more specialized bee).
Keywords: larval food; necrophagy; stingless bees; stored food; Trigona hypogea